Cleft lip and palate: from diagnosis to treatment. Literature review (Research, Society and Development, 2022)
Dental surgeries are routine procedures in offices and hospital environments. Cleft lip and palate is a congenital malformation of variable presentation that occurs during the development of the embryo, it is a more common disease than we can imagine, where it ends up having a social impact. This article exemplifies the types of clefts, diagnoses and treatments; where 30 articles were selected for review and relate to the proposed theme. For a long time, studies have been updated, research is being developed to improve the patient's comfort and quality of life, the etiology of cleft lip and palate, the exact reason why this happened is not known, but it has been associated for many factors in its appearance, where I had some limitations, for example: difficulties in drinking, speech disorders, greater susceptibility to colds and frequent infections in the affected area. The current article reports through bibliographic research the diagnosis and treatment of cleft lip and palate. Genetic factors may be at the origin of the event. The literature reports the use of some surgical techniques, treatments and multidisciplinary follow-ups.